2010
DOI: 10.1093/intimm/dxq456
|View full text |Cite
|
Sign up to set email alerts
|

FCRLA is a resident endoplasmic reticulum protein that associates with intracellular Igs, IgM, IgG and IgA

Abstract: Fc receptor-like A (FCRLA) is an unusual member of the extended Fc receptor family. FCRLA has homology to receptors for the Fc portion of Ig (FCR) and to other FCRL proteins. However, unlike these other family representatives, which are typically transmembrane receptors with extracellular ligand-binding domains, FCRLA has no predicted transmembrane domain or N-linked glycosylation sites and is an intracellular protein. We show by confocal microscopy and biochemical assays that FCRLA is a soluble resident endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…Davis, unpublished results). Human FCRLA is predominantly found in subsets of GC B cells, mainly the proliferating centroblasts, but is expressed at some level by all B cell subsets in the tonsil, with the notable exception of PCs where it is very low/absent, (Davis et al, 2002b, Facchetti et al, 2002, Mechetina et al, 2002, Masir et al, 2004) and in freshly isolated blood B cells (Santiago et al, 2011). In mice, FCRLA is broadly expressed among peripheral B cells, being highest in PCs, but is downregulated by GC B cells (Wilson et al, 2010, Reshetnikova et al, 2012).…”
Section: Cellular Distribution Of the Fcrlsmentioning
confidence: 99%
See 2 more Smart Citations
“…Davis, unpublished results). Human FCRLA is predominantly found in subsets of GC B cells, mainly the proliferating centroblasts, but is expressed at some level by all B cell subsets in the tonsil, with the notable exception of PCs where it is very low/absent, (Davis et al, 2002b, Facchetti et al, 2002, Mechetina et al, 2002, Masir et al, 2004) and in freshly isolated blood B cells (Santiago et al, 2011). In mice, FCRLA is broadly expressed among peripheral B cells, being highest in PCs, but is downregulated by GC B cells (Wilson et al, 2010, Reshetnikova et al, 2012).…”
Section: Cellular Distribution Of the Fcrlsmentioning
confidence: 99%
“…Early studies using chimeric proteins artificially expressed on the cell surface failed to demonstrate interactions with Igs (Facchetti et al, 2002); however, immunoprecipitation of endogenous FCRLA disclosed its co-association with intracellular IgM, IgG, and IgA in cell lines as well as in primary B cells (Wilson et al, 2010, Santiago et al, 2011). The elevated expression of FCRLA in GC B cells, together with its ability to bind multiple isotypes of intracellular Ig, suggests a possible role for FCRLA in Ig retention during affinity maturation.…”
Section: Emerging Fcrl Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, FcRL6 has been reported to bind HLA-DR (24), and we and others have shown that intracellular FcRLA associates with multiple Ig isotypes within the lumen of the endoplasmic reticulum (25, 26). Given the homology of FcRL3-5 with FcγRI and the association between FcRLA and Igs, we decided to examine whether any of the FcRL proteins could bind Ig.…”
Section: Introductionmentioning
confidence: 96%
“…The intracellular TRIM21 receptor is involved in proteasomal targeting of IgG opsonized virus(93). Other IgG binding proteins, such as as Fcγ binding protein (FcγBP), which associates with mucus at epithelial barriers(93, 94), and FcR-like (FcRL) receptors 4,5, and A(95, 96) are all known to bind IgG, but remain poorly characterized. The role these and other IgG receptors may play in determining the disposition of Ab-opsonized virus or infected cells in HIV remains to be determined.…”
Section: Fc Receptorsmentioning
confidence: 99%